Dementia in the Elderly: Social Activities in the New Era - Hoontrakul, Duangporn; Kumniyom, Nutda; Rattana-umpa, Juthamas (NU Journal of Nursing and Health Sciences, 2023)
The COVID-19 pandemic has resulted in a new way of life, and reduced social activities together, especially the older adults who are in high-risk groups. Social activity is an important activity that prevents the development of Dementia in the elder. Professional nurses should encourage the elders to adapt to their new normal lifestyles. By adjusting the way of eating, sleeping, exercising, controlling sugar cholesterol, and blood pressure, and participating in social activities. The form of social activities in the new normal era is the use of technology as a tool to enhance the cognitive skills of the elders. By communicating with friends and family members, playing games, exercising, and learning new things through mobile devices, and various applications. Regular interaction improves the cognitive functioning of the brain. Reduce the risk of developing dementia and enhance the quality of life of the older adults.